THE "SOFT POWER" FACTOR IN UZBEKISTAN’S FOREIGN POLICY: PROBLEMS AND OPPORTUNITIES. - Normurodova , Aziza Bahodir qizi (GOLDEN BRAIN, 2024)
This article examines the role of soft power in Uzbekistan’s foreign policy, highlighting both challenges and potential benefits. Soft power, defined as the ability to shape preferences through appeal and attraction rather than coercion, is increasingly significant in the global diplomatic landscape. For Uzbekistan, a nation strategically located in Central Asia, leveraging cultural diplomacy, educational exchanges, and media influence can enhance its international standing and foster stronger bilateral relations. Key opportunities for Uzbekistan include promoting its rich cultural heritage, increasing its presence in international educational institutions, and harnessing the potential of its youth in technology and innovation. These efforts can improve its image and foster goodwill among other nations. However, challenges persist, such as overcoming negative perceptions rooted in past political issues, addressing internal socio-economic disparities, and ensuring consistent policy implementation. The article argues that while Uzbekistan has made strides in utilizing soft power, a coherent and strategic approach is essential to maximize its impact. This involves not only promoting positive aspects of Uzbek culture and policy but also addressing underlying domestic issues that could undermine its credibility on the global stage. By navigating these challenges effectively, Uzbekistan can strengthen its soft power and play a more influential role in regional and global affairs.